KORELASI KADAR KALSIUM ION SERUM DAN RASIO KALSIUM/KREATININ URIN DENGAN DENSITAS MASSA TULANG PADA WANITA PERIMENOPAUSE DAN PASCAMENOPAUSE - , Riswan Hadi Kusuma ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Osteoporosis is a systemic bone disease characterized by decreased bone mass density and deterioration of bone microarchitecture so that bones become brittle and break easily. Osteoporosis common in perimenopausal and postmenopausal women. Gold standard diagnosis of osteoporosis is to assess bone mineral density (BMD) using dual x-ray method absorbtiometry (DEXA), but there are limitations to access it. Calcium is a marker of bone resorption that can be measured in serum and urine samples. The purpose of this study to determine the correlation of serum levels of calcium ions and urinary calcium/creatinine ratio (UCa/UCr) with BMD. Methods: The study design was cross-sectional. Subjects were women aged 45- 75 years, and then examined serum and urine calcium ion, serum and urine creatinine, calculating the ratio of UCa/UCr and BMD measurement using DEXA method. Results: The total number of subjects are 63 (21 normal subjects, 22 osteopenia and 20 osteoporosis). There are negative correlation was found between BMD with age (r=-0.591